Framing reciprocal obligations within intergenerational relations in Ghana through the lens of the mutuality of duty and dependence. (August 2022) - Twum-Danso Imoh, Afua
Reciprocity has long been recognised as a key feature in intragenerational relations amongst kin, affines and trading partners, but also in intergenerational relations, especially those between children and their caregivers in diverse societies. This paper seeks to explore reciprocity as the tie that binds relationships between caregivers and children while the latter are still 'dependents' and the consequences for both parties when this tie is broken. Data presented were collected from two mixed-method studies undertaken in Ghana. The findings indicate the importance of linking studies of childhoods within this context to indigenous moral and ethical frameworks about personhood and its associated features relating to the mutuality of both duty and dependence, reciprocity, relatedness, and collectivism. Failure to make these connections between children's lives in this context and the broader belief systems and their attendant moral frameworks that continue to underpin conceptualisations of childhood and intergenerational relationships results in depictions of African childhoods that are partial, limited and out of context.